A new gate drive for a single-phase matrix converter - Rahimi Baharom; Nor Farahaida Abdul Rahman; Muhamad Nabil Hidayat; Khairul Safuan Muhammad; Mohammad Nawawi Seroji; Nor Zaihar Yahaya (Institute of Advanced Engineering and Science, 2020)
This paper presents the new generation of advanced gate driver circuit based on IR2110 device for a Single-Phase Matrix Converter (SPMC) circuit topology that uses MOSFETs or IGBTs switches. The new generation of gate drive circuit uses less number of components, since a single IR2110 device can drive two power switches, thus reduce power losses and minimize the complexity of conventional circuit. An additional isolation of the upper and lower sides of IR2110 device features additional protection to the proposed gate drive system. As a result, the proposed gate drive circuit just uses four IR2110 gate drives in order to control eight switches of SPMC circuit, thus, solve the conventional bulky gate drive circuit problem in SPMCs operation. This is in line with the international power electronic technology road-maps to reduce losses, cost, volume, therefore to raise up the power density of power electronics converters. Validation have been done through the experimental test-rig. As a result, such new theoretical enhancements can be used as a novel foundation of future high power density of SPMC circuit topology and in-line with the Fourth Industrial Revolution (IR 4.0) which were characterized mainly by advances in technology